APPLIED FOOD PHOTOGRAPHY FOR GOODFELLAS RESTO WITH STILL LIFE APPROACH - Kurniawansyah, Hendrik (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
Goodfellas Resto is a restaurant with a luxurious and upscale atmosphere during the Dutch era. The concept of a mixture of urban and classic is the hallmark of the restaurant which is operated in a cultural heritage building by the famous architect Thomas Karsten. Along with the increasing competition in the restaurant business, coupled with the rampant promotion of food menus from various new restaurants, several long-established restaurants have to maintain their existence. From this problem, Goodfellas intends to re-photograph the mainstay menu, new menu, and several promo menus for the event and promote it. The method used includes 3 stages of the process, namely 1) the pre-production process includes; data collection, SWOT analysis and setting goals. 2) the production process includes; image capture and printing process. 3) post production process includes; media validation and printing of food photography media. The resulting work consists of food photography that carries a still life approach.